Pembayaran Mahar Secara Cicilan Dalam Perkawinan Menurut Pandangan Imam Syafi’i - Yuvira Andini Lubis; Alang Sidek; Suaib Lubis (Journal Smart Law, 2023)
Marriage in Islam is seen as an ideal relationship to unite only men and women, but marriage is a social bond with duties and responsibilities that are obligatory between husband and wife. These two things sometimes become a material and moral burden, especially for men in general. Payment of the dowry can be done according to ability or adapted to the circumstances and customs of the community. The dowry can be carried out or given in cash or debt, whether you want to pay in part in cash and in part in debt. The factors that push the dowry to be owed or paid in installments are economic factors that make the man object, where a prospective husband cannot give it in cash, and the factor that causes the dowry to be owed is that the dowry requested by the woman is too high because the dowry is too high. what he asked for was the dowry he dreamed of. The method used in this research is a qualitative method, namely more emphasis on aspects of in-depth understanding of a problem. Data analysis using descriptive methods. This type of research is normative legal research that examines literature studies, namely research with secondary data (literature review). The results of this research explain that payment of the dowry in installments according to Imam Syafi'i allows the suspension of all or part of the dowry for a known period of time.